AN ANTHOLOGY OF VISUAL IMAGERY, ALLUSION, AND SYMBOLIC MEANING IN TAYLOR SWIFT’S THE TORTURED POETS DEPARTMENT - Max, Jonathan Irene Sartika Dewi (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This research investigates the system of visual imagery in Taylor Swift's 31-track album, “The Tortured Poets Department: The Anthology.” It aims to analyze how Swift utilizes visual imagery and allusions not as mere decoration but as a functional system to elevate personal narratives of heartbreak and fame into archetypal explorations of suffering and survival. Employing a qualitative method with a semiotic approach, the study conducts a close reading of the album’s lyrical content. It also examines the motifs of performance and spectacle, which expose the painful dissonance between a public persona and a private self; the theme of subverted domesticity, where traditional images of home and love are corrupted; the feeling of cosmic alienation; and finally, the self-referential meta-narrative of creation, which tracks the process of transforming pain into art. The findings reveal that the visual imagery creates a claustrophobic emotional world, framing personal pain within universal mythological and literary contexts to legitimize it. This research concludes that Swift uses this visual lexicon to transform personal agony into a shared, survivable artifact, thereby positioning the artist as a healer and affirming the significance of popular song lyrics as a rich text for academic inquiry.